Lysine-mediated hydroxyethyl starch-10-hydroxy camptothecin micelles for the treatment of liver cancer - Guofei Li; Mingming Zhao; Limei Zhao (Taylor & Francis Group, 2020)
Liver cancer is a malignant tumor with extremely high morbidity and mortality. At present, traditional chemotherapy is still the most commonly used therapeutic approach. However, serious side effects lead to the treatment of liver cancer is not ideal. Therefore, it is imperative to develop a new drug delivery system based on nanotechnology and liver cancer microenvironment. In this study, a pH/reduction/α-amylase multi-sensitive hydroxyethyl starch-10-hydroxy camptothecin micelles (HES-10-HCPT-SS-Ly) targeting over-expressed amino acid (AA) transporters on the surface of liver cancer cell by applying lysine were successfully synthesized. The prepared micelles showed regular structure, suitable particle size, and intelligent drug release property. Compared with conventional HES-10-HCPT micelles and 10-HCPT injection, HES-10-HCPT-SS-Ly micelles demonstrated better in vitro anti-proliferative capability toward human liver cancer Hep-G2 cells and greater antitumor efficiency against nude mouse with Hep-G2 tumor. These findings suggest that HES-10-HCPT-SS-Ly micelles may be a promising nanomedicine for treatment of liver cancer.